Utilization of wheat straw in Ethiopia - Said, A.N.; Tolera, Adugna (Institute of Agricultural Research, 1991)
Looks into the prospects for the utilization of wheat straw in Ethiopia. Discusses production, utilization and constraints to utilization of wheat straw. Examines the effect of botanical composition and extent of lignification on wheat straw utilization, physical attributes of the straw components, and effect of varietal differences on heat straw utilization. Discusses the prospects for wheat straw utilization with particular reference to smallholder and large-scale farms, supplenentation, concentrate supplements, supplements with forage and browse legumes, agronomic practices (nitrogen fertilization) undersowing wheat with forage crops, plant breeding and selection and generous feeding to allow selective consumption. Includes data on yield, chemical composition energy content, animal performance, digestibility & feed intake.